The role of language transfer in the english learned at the advanced level at the Foreign Language Department of the University of El Salvador, main campus, during the academic year 2016 - Martínez de Portillo, Sandra Carolina; Portillo Arrazábal, Sergio de Jesús (2024)
Learning a new language is always a big challenge. Throughout history, many and different strategies have been developed in order to learn in the best possible way. The methods, over the years, have been constantly changed and improved. A common concern of the methods used to teach or to learn a new language has been the role of the first language of a learner, during the learning of a new language. This is taken in account seriously because this language L1 (mother tongue or first language) will have an impact in the learning of the target language, L2. This is due the way we process the inputs of a new language during its learning. However, the scenario becomes quite different when there is already a previous knowledge of two languages during the learning of a new language, L3. Given the fact that the knowledge of previous languages have an influence upon the learning of a new language, this impact in the target language is called “transfer”. According to Peuker (2015), the transfer effects in multilingual language development, have been studied since, at least, 50 years ago. A series of experiments about memory and learning theory (Brown 1958; Keppell & Underwood 1962; Murdock 1961; Peterson & Peterson 1959) produced the first investigations about the effects of language transfer. From its inception, the transfer was typified as a negative effect in the learning process and several forms of negative transfer were called “interference”. It was not until 1963, when Vildomec studied the positive transfer effects and appreciate it as a “facilitation” in the learning process. Consequently, all the previous languages, that a subject already speaks, will have an impact in the learning of new languages. This situation is faced by all the students from the Foreign Language Department of the University of El Salvador without exception. The students of Modern Languages, in particular, meet this scenario, for they are exposed to the learning of two new languages at the same time in the course of its major. According to this scenario, the students of modern Languages are the ones who face directly the sway of learning, at the same time, French and English -which are two languages with different roots- while they already speak a common mother tongue, Spanish.